Dermatofibrosarcoma protuberans of penis: Case report and literature review - Raashid, Hamid (Medknow Publications & Media Pvt Ltd, 2014)
Dermatofibrosarcoma protuberans (DFSP) is a rare mesenchymal skin tumor with intermediate to low grade malignancy and occasional distant metastasis and high rate of recurrence locally. It mostly involves trunk, extremities, scalp, and neck. This article describes a middle-aged married male with a DFSP lesion involving ventral aspect of glans and distal shaft of penis who underwent local excision and primary closure. The patient was tumor-free at three years of follow-up.